Disposition of students learning independence to support learning success during the COVID-19 pandemic - Setiawan, Yayan Eryk; Zauri, Ahmad Sufyan; Rukmigarsari, Rr. Ettie; Syaifuddin, Syaifuddin; Ilmi, Yuli Ismi Nahdiyati (Jurnal Pendidikan dan Pengajaran, 2022)
The background of this research is that online learning causes a decrease in student understanding. One of the factors that influence this decrease and increase in understanding is the student's thinking disposition. Thus, it is important to identify the dispositions needed by students to support their success in online learning. The purpose of this study was to identify the disposition of learning independence that is used as a supporter of successful online learning. The method of this research is quantitative research with a survey approach. The sample of this study consisted of 138 students of the mathematics education study program at the Islamic University of Malang. The data collected in this study are the results of filling out questionnaires and student opinions related to thinking dispositions. The data from filling out the questionnaire was analyzed by determining the number of students who chose the component of thinking disposition which aims to find out the component of thinking disposition that is most needed by students to be successful in learning online during the covid-19 pandemic. Meanwhile, students' opinions were analyzed descriptively which aims to find out the reasons students choose certain disposition components. The survey results show that there are four components of thinking disposition that are needed by students to be successful in online learning, namely: persistence, motivation, communication, and self-regulation. These four components are interrelated with each other. Someone successful in learning must have persistence, where persistence is built from motivation. Someone persistent and motivated must also be able to communicate with various parties. Persistence, motivation, and communication must pay attention to self-regulation. These four components of thinking disposition can be used to support student success.